1977
DOI: 10.1126/science.191910
|View full text |Cite
|
Sign up to set email alerts
|

A Phospholipid Derivative of Cytosine Arabinoside and Its Conversion to Phosphatidylinositol by Animal Tissue

Abstract: We have synthesized an analog (ara-CDP-DL-dipalmitin) of cytidine diphosphate diglyceride (CDP-diglyceride) in which the antitumor drug, cytosine arabinoside, is substituted for the cytidine moiety. Enzymes in rat and human liver convert this analog to phosphatidylinositol, thereby releasing cytosine arabinoside-5'-monophosphate, an obligatory intermediate in the activation of cytosine arabinoside. Unlike cytidine diphosphate diglyceride, however, ara-CDP-DL-diapalmitin is not an efficient substrate for phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…1) and placed in the reaction mixture (0.9 ml total volume). The assay is that of Rao and Strickland (13,14) except that (3.7 Ci/mol) and 1.0mM CDPdiglyceride (egg) were used. The reaction was stopped after 90 min with 20% trichloroacetic acid (as in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1) and placed in the reaction mixture (0.9 ml total volume). The assay is that of Rao and Strickland (13,14) except that (3.7 Ci/mol) and 1.0mM CDPdiglyceride (egg) were used. The reaction was stopped after 90 min with 20% trichloroacetic acid (as in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the late 1970s and early 1980s, groups began to investigate cytotoxicity after either alkyl chain additions to ara-C or conjugation of ara-C to phospholipids [59,60]. Raetz et al used natural or synthetic phospholipids to chemically modify ara-C.…”
Section: Phospholipid Ara-c Conjugatesmentioning
confidence: 99%
“…Previous investigators have had many successes with phospholipid/nucleoside analog conjugates; however, there are still improvements that can be made to these compounds [59,60,[62][63][64]73]. In our laboratory, we focused on the synthesis of a thioether phospholipid (1-S-dodecyl-2-Odecyl-thioglycero-3-phosphatidic acid) conjugated to either gemcitabine or ara-C [75].…”
Section: Phospholipid Gemcitabine and Ara-c Conjugatesmentioning
confidence: 99%
“…Finally, phospholipid-linked AraC conjugates were also developed. Following enzymolysis, these prodrugs release the monophosphate form of AraC (32)(33)(34). Although the mechanism of increased efficacy is still unknown, it has been shown that they lead to a more prolonged intracellular retention of the triphosphate (active) form than the parent AraC drug.…”
Section: Tumor Targeting Of Anticancer Drugsmentioning
confidence: 99%